Investigation of Cytotoxic, Antimicrobial and Antioxidant Activity of Echium vulgare L. Seed - Ateşşahin, Dilek Arslan; Dalkılıç, Lütfiye Kadıoğlu; Özeren, Yasemin; Dalkılıç, Semih; Çakmak, Kübra; Çiçek, Tuğrul Arslan (Uğur ÇAKILCIOĞLU, 2023)
Echium vulgare L. is a plant belonging to the Boraginaceae family and is used in traditional medicine for the treatment of various diseases, especially known for its anti-inflammatory and antioxidant properties. The aim of this study was to determine the cytotoxic activity of different concentrations of E. vulgare L. seed extracts obtained from methanol and hexane solvents on human breast cancer (MCF7) and human liver cancer (HepG2) cell lines using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. The antioxidant activity of the extract obtained from methanol and hexane at the same concentrations was determined according to the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity method. Antimicrobial activity was determined by disk diffusion method and bacteria such as Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli and Bacillus megaterium and Candida albicans microorganisms as fungi were used for the study. The highest antibacterial activity was detected against Escherichia coli (E. coli) with a zone diameter of 16±4 mm. Seed extract of E. vulgare prepared with hexane showed the most effective cytotoxic activity on HepG2 cell line with 20% cytotoxicity rate. In antioxidant activity tests, the methanol extract of E. vulgare exhibited the highest activity with 4.5% reduction. In conclusion, seed extracts of E. vulgare appear to be a potential source for both anticancer and antimicrobial therapies.
Keywords: Cancer Biology; Kanser Biyolojisi